Calcium supplementation from chicken eggshells to increase nitric oxide levels and control blood pressure in gestational hypertension - Rahmah, Aulia Agyanti; Hadisaputro, Suharyo; Ambarwati, Eny Retna (Universitas Muhammadiyah Purwokerto, 2022)
Background: Hypertension is one of the highest causes of death in pregnant women. Calcium deficiency can lead to hypertension. Chicken eggshell can be used as a natural calcium supplementation therapy in hypertension.Purpose: Analyze the effect of chicken eggshell on blood pressure through the increased nitric oxide level in gestational hypertension.Methods: This is Quasy experiment research with pretest and posttest with control group design. Respondents were ≥20 weeks pregnant women with gestational hypertension. Determination of respondents by purposive sampling obtained experimental group (n=12) and control group (n=12). 1.1 g/day of eggshell flour was given for 14 days.Result: Mean of systolic and diastolic blood pressure in experimental group decreased 14.25 mmHg or 9.5% (p=0.000) and 12.84 mmHg or 13.04% (p=0.000) after received chicken eggshell flour for 14 days compared to control group mean of systolic and diastolic blood pressure increased 1.92 mmHg or 1.35% (p=0.000) and 0.33 mmHg or 0,34% (p=0.121). Nitrit oxide level of experimental group increased 8.250 μmol/L or 20.93% (p=0.020) and control group decreased 3.083 μmol/L or 7.20% (p=0.488).Conclusion: Chicken eggshell flour affects increasing nitric oxide levels and controls systolic and diastolic blood pressure in gestational hypertension.